Biogram: jogo didático sobre drogas psicotrópicas no Ensino de Ciências Naturais - Silva, Rivanildo Barbosa da (2014)
The educational process requires the use of methodological strategies that seek to make efficient the processes of teaching and learning. This study has as objective to verify the didactic potential, the game "Biogram - Drugs," for the development of psychotropic drugs on learning in the discipline of Natural Science in Elementary Education. For this game "Biogram" was applied to a class of 9th grade at a public school in the state of Ceará. The research is characterized by a qualitative approach, as well as descriptive and explanatory typology. To collect data, a questionnaire to students before the match was applied, and focus groups were conducted after the game application in order to identify the influence of the design of the students about drugs and games, as well as to know their opinion about the game "Biogram - Drugs". The data were transcribed, organized and analyzed. The analysis was performed by analysis technique content based on Bardin (2011), and occurred in three stages: pre-analysis; exploration of the material; treatment and interpretation of results. To analyze the data was chosen to categorical analysis through thematic units record. It was found that the students found the "Biogram - Drugs" an interesting, fun and help